Economics of maize cultivation at selected intensive areas of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2024)
The study was undertaken to assess the input used pattern and profitability of maize in selected intensive maize-growing areas of Bangladesh from February to July 2019. The present study was conducted in four districts viz. Chuadanga, Jhenaidah, Meherpur and Kushtia were located at AEZ-11, an intensive maize-growing area. In this study, 160 farmers were selected, of which 40 from each district were randomly selected for data collection. The average farm size was 0.64 ha, whereas the maize cultivated area was 0.34 ha. It was observed that maize was cultivated from November to December in the study area. The average per hectare seed required was 20 kg ha-1 and the fertilizer requirement was 1532 kg ha-1. The average labor required was 275 man-days in a season due to less use of technology. Total production cost was Tk. 162047 ha-1, in which variable cost was Tk. 101066 ha-1 (62%) and the fixed cost was Tk. 60980 ha-1 (38%). The price of the main maize grain at Farmgate was Tk. 18 kg-1. The gross margin was Tk.1 91962 ha-1 and the net margin was Tk. 40515 ha-1 average. The benefit-cost ratio on a cash-cost basis was 1.90 and on a total-cost basis was 1.18, meaning maize cultivation was profitable. Land preparation, seed, organic manure, TSP, Urea, MoP, DAP, Gypsum, Zinc and Boron had a positive influence on maize production. The high price of fertilizer and seed was the main problem farmers faced and due to high demand, there were no marketing problems. Though it had some problems, maize cultivation overall was a profitable crop.Int. J. Agril. Res. Innov. Tech. 13(2): 70-78, Dec 2023